MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI PENDEKATAN MATEMATIKA REALISTIK DENGAN MODEL KOOPERATIF TIPE STAD - Prihatin Ningsih Sagala; Yunita Eunike Maduma (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2017)
This study aims to determine whether through the application of a realistic mathematical approach with cooperative learning model of Student Teams Archievement Division type (STAD) can improve students’ mathematical problem solving skill on algebraic operation material on the eighth class of SMP Negeri 37 Medan. The type of this study is a Classroom Action Research (PTK). The subject in this research is thirty six students of VIII-5 class of SMP Negeri 37 Medan and the object of this research is the students’ mathematical problem solving skill on algebraic operation material in VIII-5 class of SMP Negeri 37 Medan academic year 2017/2018. This study is a classroom action research (PTK) consisting of two cycles, each consisting of two meetings. Before giving an action, a diagnostic test is given first and each end of cycle is given a problem-solving test. From the results of data analysis of diagnostic tests obtained by the number of students who achieve mastery learning from diagnostic tests that is eighteen from thirty six students or 50% with the average class 57.85. The result of data analysis on the first cycle after applying realistic mathematics approach with STAD type cooperative learning model shows that the number of students who reach the completeness of learning is twenty four from thirty six students or 66.67% with the average class 69.31. The result of the final data analysis of the second cycle with the same learning obtained by the number of students reached the learning completeness that is thirty one from thirty six students or 86.11% with the average class 77.92. It means that there is an improvement in the students’ problem solving skill from the first cycle to the second cycle. Based on the classical learning completeness criteria, this learning has reached the target of learning completeness. Thus it can be concluded that the application of realistic mathematical approach with STAD type cooperative learning model in the eighth grade of SMP Negeri 37 Medan can improve students’ mathematical problem solving skills.